2014
DOI: 10.3892/br.2014.388
|View full text |Cite
|
Sign up to set email alerts
|

Circulating SFRP1 promoter methylation status in gastric adenocarcinoma and esophageal square cell carcinoma

Abstract: The secreted frizzled-related protein 1 () gene plays an important role in carcinogenesis of digestive system cancer. Previous studies proved that circulating DNA promoter methylation may be a suitable biomarker for cancer patients. The aim of the present study was to investigate whether the promoter methylation status of serum is a potential biomarker for gastric adenocarcinoma (GAC) and esophageal square cell carcinoma (ESCC). The blood samples obtained from 42 GAC and 36 ESCC patients were detected for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…In addition, we confirmed that in breast cancer the downregulation of SFRP1 associated with promoter methylation. Several groups have proposed the use of SFRP1 promoter methylation as a cancer biomarker, and our study provides further support for this concept 20 21 22 23 24 .…”
Section: Discussionsupporting
confidence: 80%
“…In addition, we confirmed that in breast cancer the downregulation of SFRP1 associated with promoter methylation. Several groups have proposed the use of SFRP1 promoter methylation as a cancer biomarker, and our study provides further support for this concept 20 21 22 23 24 .…”
Section: Discussionsupporting
confidence: 80%
“…In addition, of these 83 articles, 24 articles focused on CRC (4,5,9,3035,7285,93), 4 on leukemia (13,55–57), 4 on lung cancer (58,59,61,68), 8 on HCC (8,4954,88), 6 on esophageal cancer (EC) (3742,87), 9 on gastric cancer (GC) (5,39,4347,84,92), 5 on BC (3,18,19,28), 4 on renal cell carcinoma (RCC) (68–71) and the remaining 21 on other types of cancer. A single article evaluated SFRP methylation levels in esophageal cancer and GC (39), and 1 article evaluated SFRP methylation levels in GC and CRC (5). The information on SFRP1, SFRP2, SFRP4 and SFRP5 methylation was collected from eligible studies and presented in Table SI.…”
Section: Resultsmentioning
confidence: 99%
“…Such methylation events include hypermethylation of genes SFRP1, CASZ1, CDH13, ING2, DKK-3, TAC1, etc. (45)(46)(47)82).…”
Section: Clinical Implications Of Dna Methylation Change In Esccmentioning
confidence: 99%